Effect of supplemental feeding on habitat and crop selection by wild boar in Sweden. Issue 1 (2nd January 2023) - Muthoka, Cecilia M.; Andren, Henrik; Nyaga, Justin; Augustsson, Evelina; Kjellander, Petter
Abstract : The wild boar population has increased rapidly during the last 2 decades in Southern and Central Sweden. This rise in population size has caused severe damages to agricultural fields through their foraging behavior. Given the hierarchical nature of habitat and resource selection, wildlife management needs to understand the selection on both levels to better understand the ecology of nuisance species and mitigate the damages they infer. Thus, there is an urgent need for more knowledge on the factors that influence habitat selection as a tool in the evidence-based management of wild boar to reduce the losses they cause in the agricultural sector. This study aims to evaluate a common management action (feeding stations) influencing wild boar selection of (1) habitats and (2) resources i.e., crop types, in South-Central Sweden during summer. Eleven wild boars were fitted with GPS/GSM-collars to record movement among different habitats and crops. Wild boar shows a high preference for clear-cuts, agricultural fields, and deciduous forests. The animals showed a high preference for crop fields with oat, spring wheat, and mixed crops. A binary logistic model revealed both a positive and negative significant influence of distance to feeding stations on the selection of different habitats and crop fields. In general, feeding stations influenced the selection of different habitats and crops negatively i.e., the closer a habitat or crop field is to a feeding station, the higher the likelihood of its selection. The study recommends adjustments to wild boar management and cropping systems to reduce damages on highly selected crop fields.